2008
DOI: 10.1111/j.1743-6109.2008.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ET-1/ETA Pathway Contributes to Erectile Dysfunction Associated with Mineralocorticoid Hypertension

Abstract: Introduction The cavernosal tissue is highly responsive to endothelin-1 (ET-1), and penile smooth muscle cells not only respond to but also synthesize ET-1. Aim Considering that ET-1 is directly involved in end-organ damage in salt-sensitive forms of hypertension, we hypothesized that activation of the ET-1/ETA receptor pathway contributes to erectile dysfunction (ED) associated with mineralocorticoid hypertension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 43 publications
4
44
0
11
Order By: Relevance
“…ET-1 has been hypothesized to be directly involved in end-organ damage in saltsensitive forms of hypertension. In support of this hypothesis, Carneiro et al (2008b) found that activation of the ET-1/ET A pathway contributed to mineralocorticoid hypertension-associated ED. ET A receptor blockade may thus represent an alternative therapeutic approach for ED associated with salt-sensitive hypertension and in pathological conditions in which increased levels of ET-1 are present.…”
Section: B Endothelinsmentioning
confidence: 71%
“…ET-1 has been hypothesized to be directly involved in end-organ damage in saltsensitive forms of hypertension. In support of this hypothesis, Carneiro et al (2008b) found that activation of the ET-1/ET A pathway contributed to mineralocorticoid hypertension-associated ED. ET A receptor blockade may thus represent an alternative therapeutic approach for ED associated with salt-sensitive hypertension and in pathological conditions in which increased levels of ET-1 are present.…”
Section: B Endothelinsmentioning
confidence: 71%
“…Several studies have underlined the potential importance of ET-1 in the modulation of corpus cavernosum (CC) smooth muscle tone (60), since these cells can synthesize ET-1. The fetal human and adult penile cells, and several animal species, also express endothelin converting enzyme 1, the endothelin recepotors A (ETA) and B (ETB) subtypes (61)(62)(63). Furthermore, Melegy et al showed that ET-1 levels were significantly greater in patients with ED than the normal group (64).…”
Section: Hypertension and Edmentioning
confidence: 99%
“…Deoxycorticosterone acetate-salt-induced hypertensive animals showed increased cavernous contractile responses to both ET-1 and the a-adrenergic receptor agonist phenylephrine. 113,114 As to the downstream signaling, although protein expression levels of ROCK in the CC of deoxycorticosterone acetate-treated animals were similar to those of control animals, the phosphorylated form of myosin phosphatase regulatory subunit, a downstream effector of ROCK, was increased in cavernous tissue from deoxycorticosterone acetate animals. 114 In the spontaneously hypertensive rat, Wilkes et al 115 found that hypertension-related ED is associated with elevated penile RhoA levels and that inhibition of ROCK activity with Y-27632 was beneficial in attenuating the decline in erectile function.…”
Section: Contractile Signaling and Edmentioning
confidence: 99%